Implementasi Penilaian Dribble Bola Basket Berbasis Website pada Pembelajaran Bola Basket Siswa - Tio Fajar Fitrianto; Muchamad Arif Al Ardha; Nurhasan; Sauqi Sawa Bikalawan; Jihan Dwi Wulandari; Putri Nur Alifah (MAN Insan Cendekia Jambi, 2026)
The development of digital technology in recent decades has driven a paradigm shift in sports evaluation from conventional methods to a data-driven performance approach. This study aims to develop and evaluate the feasibility of a web-based basketball dribble assessment system to support teacher performance. This study uses a Research and Development (R&D) approach with the ADDIE model integrated with formative evaluation. The research subjects consisted of web media experts, learning experts, basketball experts, and five junior high school physical education (PJOK) teachers selected using random sampling as end users. Data were collected using a content validation assessment sheet and a Likert scale questionnaire. The expert validation results showed a Scale-Content Validity Index (S-CVI) value of 0.97, indicating that the product has very strong content validity and is categorized as very feasible. Meanwhile, the results of user trials showed that the system obtained an overall average score of 4.58, categorized as very feasible. In detail, user assessments included aspects of appearance (4.48), material content (4.48), construction (4.68), and teaching relevance (4.68). This shows that the website-based basketball dribble assessment system is very feasible and has the potential to become an alternative evaluation solution that is objective, efficient, and digitally integrated in schools.